American Institute of Laundering Convention (circa 1950s) - Hercules Incorporated (1950)
General view of several exhibition displays at the American Institute of Laundering convention held in Atlantic City, New Jersey advertising Carco CMC (sodium carboxymethylcellulose) for use in detergents.
Keywords: Advertising; Advertising, Industrial; Trade shows; Chemical industry; Corporations; Laundry; Laundry industry; American Institute of Laundering; Detergents